Modernism and short narrative genres evolution. Talking of Alfonso Hernández Catá - Martínez Arnaldos, Manuel (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
The author of the present article studies the evolution of tales and more especifically short stories under the auspices of Modernism. Using as a referent the short narrative production of the spanish-cuban writer Alfonso Hernández Catá (1885-1940), as well as his theoretical considerations, the transformation of such genre forms is analysed from very different perspectives raging from the consolidated positions of realism and naturalism to the code break imposed with Modernism. The theoretical and practical concern of Hernández Catá for strictly demarcating the boundaries between the tale and short story, together with the search for. a vew both aesthetic and formal artistic ideal, in accordance with the cultural space of the first 20th century decades, are assessed.